2021
DOI: 10.1155/2021/6652960
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation Method of Rock Mass Stability Based on Natural Frequency

Abstract: The limit equilibrium method’s analysis index cannot be measured by on-site monitoring equipment and cannot be used for monitoring and early warning of rock instability. The existing rock stability evaluation methods based on vibration information cannot evaluate the stability of rocks quantitatively. In this paper, the slope’s constraints on the rock were simplified to springs and a three-dimensional analysis model of rock vibration was established. The equation for calculating the natural frequency of rock t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In order to achieve the stability evaluation of the perilous rock, Jia et al (2023aJia et al ( , 2022 found that the natural frequency increases nonlinearly in the horizontal direction with the increasing buried depth of the unstable rock, and they established the quantitative relationship model between the safety factor and natural frequency. Xie et al (2021) established a three-dimensional (3-D) analysis method for the rock vibration, and they proved the effectiveness for the rock stability analysis based on the natural frequency. At present, investigations on the natural frequency of rock primarily concentrate on the field or laboratory scales, such as seismic failure of rock slopes (Song et al 2019a) and rock block's instability (Jia et al 2017(Jia et al , 2019(Jia et al , 2023b, which are characterized by much smaller pores relative to the size of a rock to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve the stability evaluation of the perilous rock, Jia et al (2023aJia et al ( , 2022 found that the natural frequency increases nonlinearly in the horizontal direction with the increasing buried depth of the unstable rock, and they established the quantitative relationship model between the safety factor and natural frequency. Xie et al (2021) established a three-dimensional (3-D) analysis method for the rock vibration, and they proved the effectiveness for the rock stability analysis based on the natural frequency. At present, investigations on the natural frequency of rock primarily concentrate on the field or laboratory scales, such as seismic failure of rock slopes (Song et al 2019a) and rock block's instability (Jia et al 2017(Jia et al , 2019(Jia et al , 2023b, which are characterized by much smaller pores relative to the size of a rock to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [ 24 ] created a technique to assess a slope rock mass’s stability using LDV and examined the quantitative correlation between the vibration characteristics and rock mass stability. Several scholars [ 42 , 43 , 44 ] have applied LDV to study unstable rock masses and achieved good results. At present, LDV monitoring technology has not yet been used in the staged damage progress of rocks with different brittleness degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Du et al simulated the process of landslides through experiments and found that the natural frequency and damping ratio of unstable rock decrease with the decrease in the contact area between unstable rock and bedrock mass [16]. Xie et al proposed a method to calculate the stability coefcient of unstable rock mass based on natural frequencies [17]. Tanaka et al pointed out that the diference in vibration modes of a dangerous rock mass can refect its stability [18].…”
Section: Introductionmentioning
confidence: 99%